Novel Delivery Systems of Raloxifene Hydrochloride for Improved Bioavailability and Therapeutic Efficacy: A Review - Chaturvedi, Shashank; Sharma, Richa (Drug Delivery Letters, 2025)
Raloxifene hydrochloride belongs to the selective estrogen receptor modulator category. Initially, US FDA approved its use for the prevention and treatment of osteoporosis in post-menopausal women. Later, raloxifene hydrochloride was also approved for the prevention of invasive breast carcinoma in post-menopausal women under the high-risk category. Despite its immense and diverse therapeutic potential, the oral bioavailability of raloxifene hydrochloride is only 2%. The factors responsible for the poor bioavailability of raloxifene hydrochloride include its amphiphobic nature, para-glycoprotein pump-mediated efflux in the intestine, and high pre-systemic glucuronidation. In the past two decades, multiple novel delivery systems, viz. lipid-based nanocarriers, polymeric nanoparticles, polymer-lipid hybrid nanoparticles, micelles, and mixed micelles, have been developed to overcome its drawbacks. Moreover, inclusion complex, phospholipid complex, and solid dispersion have also been developed to improve its solubility and dissolution rate. Further, some research groups successfully explored non-peroral routes like nasal and transdermal for augmenting the raloxifene hydrochloride bioavailability and its therapeutic efficacy. Hence, the principal objective of this review paper is to critically analyze all the delivery systems developed for raloxifene hydrochloride with their advantages and limitations. In addition, a detailed discussion of the physicochemical and pharmacokinetic parameters of raloxifene hydrochloride has been included in this paper. An in-depth understanding of these parameters will assist formulation scientists in developing efficient delivery systems in the future. In conclusion, the literature review revealed that the nanoparticulate systems successfully augmented the raloxifene hydrochloride bioavailability and therapeutic efficacy in pre-clinical experiments. However, future clinical trials should be conducted to assess their safety and therapeutic efficacy for rapid pre-clinical to clinical translation.
Keywords: breast cancer